Research on the impact of internet use on fertilizer and pesticide inputs: Empirical evidence from China - Hui Na; Jiaxi Kang (Heliyon, 2023)
Fertilizers and pesticides are important agricultural production materials. Excessive use of fertilizers and pesticides can cause negative impacts such as decline in the quality of farm products and damage to the ecological environment. Increasing the efficiency of fertilizers and pesticides is an important step to accelerate the green transformation of agriculture. Using data from the 2015 China Household Finance Survey, this paper analyzes the impacts of Internet use on fertilizers and pesticides by farmers, and the mechanism behind the action with the help of the propensity score matching method and the instrumental variable method. The findings are: (1) Farmers who use the Internet have greater inputs of fertilizers and pesticides compared to farmers who do not use the Internet. (2) Farmers who do not use the Internet would have their inputs of fertilizers and pesticides increased by 21.9% and 47.7%, respectively, if they had used the Internet under the counterfactual hypothesis. (3) In the heterogeneity analysis, Internet use plays a positive and significant role in the inputs of fertilizer and pesticide in the eastern part of China, and Internet use has greater impact on pesticide inputs than on fertilizer in central and western regions. (4) Internet use has a positive and significant effect on fertilizer and pesticide inputs in both lower scale and higher scale operations, and a positive but not significant effect in moderate-scale operations.